Association of prenatal phthalate exposure with pubertal development in Spanish boys and girls - Freire, Carmen; Castiello, Francesca; Lopez-Espinosa, Maria-Jose; Beneito, Andrea; Lertxundi, Aitana; Jimeno-Romero, Alba; Vrijheid, Martine; Casas, Maribel (Environmental research, 2022)
Phthalates are widespread, anti-androgenic chemicals known to alter early development, with possible impact on puberty timing. To investigate the association of prenatal phthalate exposure with pubertal development in boys and girls. Urinary metabolites of six different phthalate diesters (DEP, DiBP, DnBP, BBzP, DEHP, and DiNP) and non-phthalate plasticizer DINCH® were quantified in two urine samples collected during pregnancy from mothers participating in the INMA Spanish cohort study. Pubertal assessment of their children at age 7–10 years (409 boys, 379 girls) was conducted using the parent-reported Pubertal Development Scale. Modified Poisson and Weighted Quantile Sum (WQS) regression was employed to examine associations between prenatal phthalates and risk of puberty onset, adrenarche, and gonadarche. Effect modification by child weight status was explored by stratified analysis. Prenatal exposure to DEHP was associated with higher risk of puberty onset (relative risk [RR] = 1.32, 95% CI = 1.09–1.59 per each log-unit increase in concentrations) and gonadarche (RR = 1.23, 95% CI = 1.00–1.50) in boys and higher risk of adrenarche (RR = 1.25, 95% CI = 1.03–1.51) in girls at age 7–10 years. In boys, prenatal exposure to DEP, DnBP, and DEHP was also associated with higher risk of adrenarche or gonadarche (RRs = 1.49–1.80) in those with normal weight, and BBzP and DINCH® exposure with lower risk of adrenarche (RR = 0.49, 95% CI = 0.27–0.89 and RR = 0.47, 95% CI = 0.24–0.90, respectively) in those with overweight/obesity. In girls, DiBP, DnBP, and DINCH® were associated with slightly higher risk of gonadarche (RRs = 1.14–1.19) in those with overweight/obesity. In the WQS model, the phthalate mixture was not associated with puberty in boys or girls. Prenatal exposure to certain phthalates was associated with pubertal development at age 7–10 years, especially earlier puberty in boys with normal weight and girls with overweight/obesity. However, there was no evidence of effect of the phthalate mixture on advancing or delaying puberty in boys or girls. •MEP, MnBP, and ΣDEHP were associated with earlier puberty in normal weight boys.•ΣDEHP was associated with earlier adrenarche in girls regardless of their BMI.•MBzP and ΣDINCH were associated with delayed adrenarche in overweight/obese boys.•MiBP, MnBP, and ΣDINCH were associated with earlier gonadarche in overweight girls.•Child obesity modifies the association of prenatal phthalate exposure with puberty.